Allelopathic effect of Passiflora alata Curtis extracts on seed germination - Freitas, Allan Rocha de; Lopes, José Carlos; Mengarda, Liana Hilda Golin; Zanotti, Rafael Fonsêca; Venancio, Luan Peroni (Comunicata Scientiae, 2016)
Many plant chemical compounds can interfere on seed germination and on the development of other plants. Thus, this research aimed to verify the effect of sweet passion fruit seeds (Passiflora alata Curtis) extracts, under lettuce seed germination and lettuce seedlings growing. The experiment was carried out in a controlled environment. The treatments were: T1-distilled water as a control; T2-embryo extract; T3- tegument extract; T4- whole grain extract; T5- soaking solution. Lettuce seed (Lactuca sativa L.) cv. Babá de Verão, was used as a bioindicator of the allelopathic effect. When the treatment of embryo extract of sweet passion fruit was applied, a lower germination percentage and lower speed emergence rate of lettuce seeds were observed. The largest number of abnormal seedlings was observed from seeds germinated in the embryo extract (T2) and the soaking solution (T5). The sweet passion fruit embryo extract discloses compounds that are able to inhibit the germination and can negatively influence the development of lettuce seedlings.